Methylation Patterns of the FKBP5 Gene in Association with Childhood Maltreatment and Depressive Disorders - Nora L. Großmann; Antoine Weihs; Annemarie Luise Kühn; Susann Sauer; Simone Röh; Tobias Wiechmann; Monika Rex‐Haffner; Henry Völzke; Uwe Völker; Elisabeth B. Binder; Alexander Teumer; Georg Homuth; et al. (2024)
Childhood maltreatment is an important risk factor for adult depression and has been associated with changes in the hypothalamic pituitary adrenal (HPA) axis, including cortisol secretion and methylation of the FKBP5 gene. Furthermore, associations between depression and HPA changes have been reported. This study investigated the associations of whole-blood FKBP5 mRNA levels, serum cortisol levels, childhood maltreatment, and depressive symptoms with the whole-blood methylation status (assessed via target bisulfite sequencing) of 105 CpGs at the FKBP5 locus using data from the general population-based Study of Health in Pomerania (SHIP) (N = 203). Both direct and interaction effects with the rs1360780 single-nucleotide polymorphism were investigated. Nominally significant associations of main effects on methylation of a single CpG site were observed at intron 3, intron 7, and the 3′-end of the gene. Additionally, methylation at two clusters at the 3′-end and intron 7 were nominally associated with childhood maltreatment × rs1360780 and depressive symptoms × rs1360780, respectively. The results add to the understanding of molecular mechanisms underlying the emergence of depression and could aid the development of personalised depression therapy and drug development.